2007
DOI: 10.4049/jimmunol.178.8.5109
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Recruitment of Neutrophils to the Site of Infection Dramatically Attenuates Borrelia burgdorferi Infectivity

Abstract: Borrelia burgdorferi infection causes an initial skin lesion called erythema migrans (EM) in human Lyme disease and in models of monkey and rabbit borreliosis. EM results from the inflammatory response triggered by spirochete replication and likely develops to contain the initial infection but allows bacterial dissemination to occur. The essential lack of neutrophil involvement in EM histopathology prompted us to examine the consequence of increasing their recruitment in the inflammatory response to the Lyme d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 29 publications
3
56
1
Order By: Relevance
“…Pathogen transmission requires tick attachment for at least 36 to 48 hours for Babesia microti or B. burgdorferi and at least 24 hours for Anaplasma phagocytophilum (Piesman and Spielman 1980, Piesman 1993, des Vignes et al 2001. Furthermore, any pathogen that might be transmitted in tickimmune hosts would likely be destroyed by neutrophils and lymphocytes at the tick-dermal interface (Xu et al 2007). Inflammatory and vascular changes in the dermis provide an explanation for the decreased incidence of tick-borne disease in tick-immune mammalian hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen transmission requires tick attachment for at least 36 to 48 hours for Babesia microti or B. burgdorferi and at least 24 hours for Anaplasma phagocytophilum (Piesman and Spielman 1980, Piesman 1993, des Vignes et al 2001. Furthermore, any pathogen that might be transmitted in tickimmune hosts would likely be destroyed by neutrophils and lymphocytes at the tick-dermal interface (Xu et al 2007). Inflammatory and vascular changes in the dermis provide an explanation for the decreased incidence of tick-borne disease in tick-immune mammalian hosts.…”
Section: Discussionmentioning
confidence: 99%
“…IrLBP (I. ricinus lipocalin binding protein) binds leukotriene B4 (LTB4) and inhibits neutrophil transendothelial migration induced by LTB4 (16). This deficit in functional neutrophils at the tick bite site appears to enhance bacterial propagation and the formation of erythema migrans (17). Ribeiro and colleagues (18) have shown that I. scapularis saliva inhibits in vitro neutrophil functions, including aggregation, and phagocytosis, as well as ROS production and granule exocytosis.…”
mentioning
confidence: 99%
“…6 This effect was reversed when Borrelia-expressed KC was neutralized by anti-KC antibodies. CD14 facilitates interactions between bacterial products and the TLR signaling machinery, which promote innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the principal early infiltrating cell type observed in the infected joints of humans, 2 a finding mirrored in a mouse model of Lyme arthritis. [3][4][5][6] Depletion of neutrophils results in early onset of arthritis with a higher bacterial burden in murine Lyme borreliosis. 4 Conversely, B. burgdorferi genetically engineered to express KC (the murine equivalent of human CXCL8), a neutrophil-recruiting chemokine, is rapidly cleared from mouse tissues because of a faster and continuous influx of neutrophils to the site of infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation